2017
DOI: 10.1002/cpcy.15
|View full text |Cite
|
Sign up to set email alerts
|

Method for DNA Ploidy Analysis Along with Immunophenotyping for Rare Populations in a Sample using FxCycle Violet

Abstract: The clinical use of flow cytometric DNA ploidy assay has been extended towards stratifying the risk of diseases, such as monoclonal gammopathies or B cell acute lymphoblastic leukemia, and to detect circulating tumor cells, both of which require detection of minute cell populations. This unit describes a protocol for determining DNA ploidy in fixed samples with simultaneous surface immunophenotyping. It is an easy method for simultaneous 6- to 8-color immunophenotyping and DNA content analysis using FxCycle Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…The DNA‐ploidy is determined as a DNA‐index (DI), a ratio of the amount of nucleic acid dye binding to the tumor cells in the G0/G1 phase to that of normal cells (usually lymphocytes) with 46 chromosomes. DI≤0.95 represents hypodiploidy and DI≥1.06 represents hyperdiploidy (Darzynkiewicz, 2010; Darzynkiewicz & Juan, 2001; Tembhare et al, 2017). Recently, Gupta et al have reported a strong correlation between DNA‐ploidy analysis by FCV‐based MFC‐ploidy and cytogenetic methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA‐ploidy is determined as a DNA‐index (DI), a ratio of the amount of nucleic acid dye binding to the tumor cells in the G0/G1 phase to that of normal cells (usually lymphocytes) with 46 chromosomes. DI≤0.95 represents hypodiploidy and DI≥1.06 represents hyperdiploidy (Darzynkiewicz, 2010; Darzynkiewicz & Juan, 2001; Tembhare et al, 2017). Recently, Gupta et al have reported a strong correlation between DNA‐ploidy analysis by FCV‐based MFC‐ploidy and cytogenetic methods.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where two distinct peaks (populations) of blasts were identified, DI of both populations was calculated (Figure 1). FCV‐based MFC‐ploidy was categorized as hypodiploid, diploid, near‐hyperdiploid, hyperdiploid, near‐triploid, near‐tetraploid for DI ≤0.95, 0.96 to 1.05, 1.06 to 1.15, 1.16 to 1.39, 1.40 to 1.79, and 1.80 to 2.2, respectively, based on published literature (Darzynkiewicz, 2010; Darzynkiewicz & Juan, 2001; Gupta et al, 2019; Rachieru‐Sourisseau et al, 2010; Tembhare et al, 2016, 2017; Trueworthy et al, 1992). The results of FCM‐DNAploidy were correlated with the cytogenetic findings.…”
Section: Methodsmentioning
confidence: 99%
“…Standard fluorescence in situ hybridization (FISH) assays (Locus‐Specific Identifier (LSI) probes from Zytovision) and conventional karyotyping were performed, including t(9;22): BCR/ABL1, t(1;19): TCF3/ PBX1, t(12;21): ETV6/RUNX1, t(v;11q23): KMT2A, and trisomy/tetrasomy analyses. FxCycle Violet dye‐based flow cytometric method was used to evaluate DNA ploidy 32,33 …”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic FCM panel and sample processing protocol are as described in our previous publication 16 . In patients diagnosed with B‐ALL, an additional 5‐color FxCV ploidy tube was freshly processed with a pre‐titrated surface staining antibody ( clone ) cocktail (CD34‐PC5.5 [ 8G12 ], CD10‐PC7 [ ALB1 ], CD19‐APC [ J3‐119 ], and CD45‐APC AF00 [ J.33 ]), and FxCV dye as per protocol published by Tembhare et al 17 The processed surface antibody and FxCV‐stained cells were suspended in phosphate‐buffered saline with 0.5% bovine serum albumin and acquired immediately in BC Navios EX flow cytometer at an acquisition speed of <200 events per second with linear amplification. The list mode data files were compensated and analyzed with Beckman Coulter Kaluza (version 2.0) software as per our sequential gating strategy described in Figure 1.…”
Section: Methodsmentioning
confidence: 99%